2007
DOI: 10.1002/hbm.20393
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity of the anterior insula in emotional processing depends on the individuals' emotional susceptibility

Abstract: Differences in personality factors between individuals may manifest themselves with different patterns of neural activity while individuals process stimuli with emotional content. We attempted to verify this hypothesis by investigating emotional susceptibility (ES), a specific emotional trait of the human personality defined as the tendency to "experience feelings of discomfort, helplessness, inadequacy and vulnerability" after exposure to stimuli with emotional valence. By administering a questionnaire evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
3
18
2
6
Order By: Relevance
“…Furthermore, the strong emotional states produced by substance abuse have been proposed to enhance insula connectivity, which in turn leads to strong associations between drugs of abuse and emotional states in drug abusing subjects (Viswanath et al, 2015). Interestingly, several studies have indicated that activation in the anterior subdivision of the left insula is negatively correlated with emotional control-related neuroticism (Iaria et al, 2008; Meriau et al, 2009; Simmons et al, 2011). We speculate that the insula-neuroticism correlation we observed in AUD may reflect the same relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the strong emotional states produced by substance abuse have been proposed to enhance insula connectivity, which in turn leads to strong associations between drugs of abuse and emotional states in drug abusing subjects (Viswanath et al, 2015). Interestingly, several studies have indicated that activation in the anterior subdivision of the left insula is negatively correlated with emotional control-related neuroticism (Iaria et al, 2008; Meriau et al, 2009; Simmons et al, 2011). We speculate that the insula-neuroticism correlation we observed in AUD may reflect the same relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Tais estudos vêm sendo realizados tanto em voluntários saudáveis como em pacientes com transtorno obsessivo compulsivo (TOC), esquizofrenia, transtornos depressivos e outros Hariri et al, 2003;Banks et al, 2007;Iaria et al, 2008;Mériau et al, 2009). …”
Section: Estudos De Neuroimagem Funcional Durante Estimulação Emocionunclassified
“…Também observaram que o tamanho desta correlação poderia predizer a capacidade do indivíduo regular com sucesso um estímulo negativo (Banks et al, 2007). Iaria et al (2008), utilizando um paradigma de processamento emocional explícito com fotografias do IAPS, observaram que a atividade da ínsula encontrava-se aumentada em indivíduos saudáveis, mas com maior sucetibilidade individual de sentir desconforto e inadequação em resposta a um estímulo afetivo (Iaria et al, 2008). Mériau et al (2009) (Mériau et al, 2009).…”
Section: Estudos De Neuroimagem Funcional Durante Estimulação Emocionunclassified
See 2 more Smart Citations